Construction of News on the Impact of the Covid-19 Pandemic in Online Media Kompas.com and Republika.co.id - Habib Al Ayyubi; Totok Wahyu Abadi (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to find out how the online media Kompas.com and Republika.co.id frame news about the impact of the Covid-19 pandemic. The research method used is descriptive qualitative. The theory used is the analysis of the framing model of Zhongdang Pan and Gerald M. Kosicki. This study examines 17 news titles in the Kompas.com media and 14 news titles in the Republika.co.id media for the period between 1 March - 30 April 2020. This study shows the results that related to the impact of Covid-19, both media contain the same theme. news about social and economic impacts, but the Republika.co.id media also includes education and transportation themes. The difference between the two media is that Kompas.com includes more quotes followed by paragraphs reaffirming the sources' quotes. Meanwhile, Republika.co.id has written quite a lot of journalists' descriptions by including quotes from sources that are considered to be corroborating. Media Kompas.com in choosing news titles is clearer so that readers can immediately catch the content of the news, in contrast to Republika.co.id which in choosing titles tends to make readers feel excited about the content of the news. Kompas, which is seen as neutral and republican, which is seen as the majority media, maintains neutrality in reporting the impact of Covid-19.